2013
DOI: 10.1111/1750-3841.12218
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Communities in Pu'er Tea Samples of Different Ages

Abstract: Pu'er is a major kind of postfermented tea and is made with a "large leaf" variety of Camellia sinensis (C. sinensis assamica), whose distribution is limited to the mountains of southern Yunnan, China. The quality of Pu'er tea is believed to increase with storage (aging, maturing) because of postfermentation by microbes. The effect of storage period (from < 1 to 192 mo) on the bacteria and fungi in Pu'er tea was investigated by a culture-dependent and a PCR-DGGE method. The individual numbers of fungi and bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
(55 reference statements)
1
30
0
Order By: Relevance
“…The role of Pu-erh tea as an anti-oxidative agent for reducing cholesterol levels and aiding digestion is well acknowledged (Hou et al, 2009;Cao et al, 2011). There are two main categories of Pu-erh tea, namely raw and ripened (Tian et al, 2013). The processing of raw Pu-erh tea includes the fixation, rolling, and drying of leaves before the tea is compressed into bricks, cakes, or other shapes.…”
Section: Pu-erh Teamentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Pu-erh tea as an anti-oxidative agent for reducing cholesterol levels and aiding digestion is well acknowledged (Hou et al, 2009;Cao et al, 2011). There are two main categories of Pu-erh tea, namely raw and ripened (Tian et al, 2013). The processing of raw Pu-erh tea includes the fixation, rolling, and drying of leaves before the tea is compressed into bricks, cakes, or other shapes.…”
Section: Pu-erh Teamentioning
confidence: 99%
“…Microbiota has a significant influence on the quality of Pu-erh tea, especially during the wet piling. Various kinds of bio-techniques including DGGE (Tian et al, 2013;Yang et al, 2013), pyrosequencing (Lyu et al, 2013), metatranscriptomics (Jiang et al, 2012), metagenomics and metaproteomics (Zhao et al, 2015) have been used to investigate the microbial composition during the piling process. However, the microbiological profiles of Pu-erh tea are not well understood.…”
Section: Pu-erh Teamentioning
confidence: 99%
“…[7]. Additionally, a high level of microbiota diversity was gained using culture-independent approaches, such as denaturing gradient gel electrophoresis (PCR-DGGE) [8][9][10][11], a 16S rRNA gene clonal library [7], and pyrosequencing analyses [12,13]. Recently, we investigated the microbial communities and enzymes of an SSF processing sample of PFPT (collected on day 21) using 454 pyrosequencing and LC-MS/MS approaches [13].…”
mentioning
confidence: 99%
“…and Penicillium spp. are the filamentous fungal genera commonly associated with SSF of pu-erh tea [52][53][54], particularly A. niger, A. sydowii and A. tamarii having been widely reported as the dominant fungi in the SSF of pu-erh tea. The assessment in agar mediums with theophylline as carbon source showed that six Aspergillus isolates could survive in theophylline agar mediums, which suggested that those six candidate isolates (Table 3) could utilize theophylline as potential carbon source directly in the absence of other carbon source.…”
Section: Discussionmentioning
confidence: 99%